1999
DOI: 10.1097/00000658-199904000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cytokine Response After Gut Ischemia

Abstract: These results directly document that the levels of tumor necrosis factor-alpha and interleukin-6 released from the gut increase after an ischemic or I/R injury, such as SMAO, and that there is a relation between the magnitude of the gut ischemic or I/R insult and the cytokine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(99 citation statements)
references
References 22 publications
7
82
0
10
Order By: Relevance
“…In summary, the mRNA results of this experimental study confirm previous findings of our research group concerning the gut as a site of TNF-α and IL-6 liberation after ischemic injury [14,17]. However, an intestinal mRNA expression of cytokines IL-1 and IL-10 was not found in either of the experimental groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In summary, the mRNA results of this experimental study confirm previous findings of our research group concerning the gut as a site of TNF-α and IL-6 liberation after ischemic injury [14,17]. However, an intestinal mRNA expression of cytokines IL-1 and IL-10 was not found in either of the experimental groups.…”
Section: Discussionsupporting
confidence: 90%
“…Together with previous studies published by our research group, these findings suggest that the intestinal tract produces and liberates pro-and anti-inflammatory cytokines in a biologically active form after ischemic injury [14,17]. However, the importance of the gut as a cytokine-generating organ needs to be confined: the lung has been identified as the primary site of cytokine gene expression in this two-hit animal model of sepsis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Second, intestinal injury may expose the basolateral membrane of the intestinal epithelium expressing TLRs allowing the activation of TLR locally by commensal products leading to a systemic inXammation [3]. Third, a massive disruption of the intestinal barrier including damage to the microvasculature may allow the escape of several TLR agonists produced by intestinal commensals or a direct translocation of intestinal microbes into circulation, which lead to systemic inXammation and sepsis [28].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The majority of them were experimental studies using animal models. Fevang et al 15 found that bowel strangulation was followed by greatly increased venous concentration and release of IL-6 in the strangulated loop in a pig model.…”
mentioning
confidence: 99%